Conceptual Learning of Calculus in Teacher Education: A Time Series Approach to Visualization Over Math Solver in Diverse Learners - G, Panneerselvam; M, Priyadharsini (Cognitive Insight in Education, 2026)
The objective of this paper is to assess the ambience of diverse learners practicing the contents in calculus with Microsoft Math Solver. Calculus problems involve abstract reasoning, particularly logical reasoning and abstract thinking, as well as equations as a platform. This study's primary goal is to evaluate conceptual learning in calculus in teacher education using an exploratory approach that prioritizes visuals over conventional math solvers. Aforementioned is primarily to assess how effectively student-teachers can develop a profound, long-lasting understanding of mathematical concepts through a preferred procedure. To help achieve the goals, an exploratory survey design is employed over a specified interval of time, known as a time-series approach. The convenience sampling technique is employed in this study. This approach seeks to explain phenomena, such as calculating derivatives in the advanced computational laboratory using Microsoft Math Solver, which forms the foundation for similar concepts carried out methodically in conventional classrooms. Additionally, the description refers to using a method that involved six math majors' student-teachers in various contexts. The Hawthorne effect is mitigated in this study, as the researcher can observe students in class while they receive instruction, allowing them to focus on problem-solving. As already stated, this is also possible in an advanced computing lab. The research yielded well-resourced, self-paced questions and answers, as well as an environment that facilitated the exposure of the concept of calculus in collaboration with Microsoft Math Solver. Learners save time, increase creativity and experience, and recapitulate solutions through visualization with updated, enhanced routines. This study captures the ambiance in the visualization of learning Calculus via MMS. The sample may include student teachers, who benefit significantly from applying the subject in this way, both in their teaching practice and in the early stages of their careers. Additionally, treating student-teachers as samples in this exploratory survey is a novel aspect of this study.